Pediatric Meckel's Diverticulum: Report of 208 Cases and Review of the Literature. (3rd May 2016) - Francis, Adero; Kantarovich, Diana; Khoshnam, Nasim; Alazraki, Adina L.; Patel, Binita; Shehata, Bahig M.
ABSTRACT: We report a review of 208 cases of Meckel's diverticulum among pediatric patients from one single institution. One of the aims of this report is to highlight the different diagnostic modalities of Meckel's diverticulum since a majority of cases is undiagnosed prior to surgery. Our review shows 58 cases containing gastric and/or pancreatic heterotopic tissue, including two unique cases. The first case reported is a desmoid tumor arising at the tip of diverticulum, a case that, to our knowledge, has not been previously reported. The second case involves a female patient appearing with an acute abdomen thought to be appendicitis, instead surgery revealed a diverticulum arising from the ileum. The cause of acute abdomen was due to gonococcal infection. In conclusion, we hope that this large series of Meckel's cases will enrich our readers on the differential diagnosis and preoperative diagnostic techniques of Meckels' diverticulum.